2020
DOI: 10.18332/tid/119117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal active smoking during pregnancy on the trajectory of childhood body mass index: A multilevel analysis using quartiles of birthweight

Abstract: INTRODUCTION Maternal active smoking during pregnancy is associated with childhood obesity; however, whether maternal active smoking affects childhood body mass index (BMI) according to birthweight has not been examined. METHODS The study participants were 1955 women and their single-born infants, born between 1 April 1991 and 31 March 2003, in Koshu City, Japan, for whom complete data for birthweight, pre-pregnancy maternal BMI and pregnancy smoking status were available. Maternal smoking status during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In this regard, smoking may be a predisposing factor for abdominal obesity, glucose Our previous results suggested that maternal smoking during pregnancy was significantly associated with childhood obesity [22][23][24] . This association was observed in the second quartile of birthweight 25 . Therefore, the GWG of smoking mothers may compensate for the negative effects of maternal smoking during pregnancy on birthweight.…”
Section: Discussionmentioning
confidence: 59%
“…In this regard, smoking may be a predisposing factor for abdominal obesity, glucose Our previous results suggested that maternal smoking during pregnancy was significantly associated with childhood obesity [22][23][24] . This association was observed in the second quartile of birthweight 25 . Therefore, the GWG of smoking mothers may compensate for the negative effects of maternal smoking during pregnancy on birthweight.…”
Section: Discussionmentioning
confidence: 59%
“…Several efforts have been made to dissociate these comorbid disorders or rank their importance for the development of HS. However, these data might ignore the real-world situation, where obesity and smoking often cooccur in the same person and family members [17][18][19]. For these reasons, we conducted this study to assess the importance of metabolic disorders/obesity, smoking/environmental toxins, and inflammation in HS by utilizing the differential expression of major relevant protein markers in lesional skin of obese/smoking versus non-obese/nonsmoking HS patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown significant links between maternal smoking during pregnancy and adverse child growth outcomes, including a higher likelihood of low birth weight and impaired linear growth. [ 30 31 ] Another limitation of the study is the absence of data on breastfeeding habits in the dataset on the possible impact on the observed growth patterns. A prior Jordanian study revealed a low breastfeeding rate, indicating that only 24% of infants were breastfed at 2–3 months of age.…”
Section: Discussionmentioning
confidence: 99%